Biotin-triggered release and transfection of DNA complexes immobilized on a substrate via biotin–avidin interaction. (May 2014) - Wang, Chunfen; Li, Luyan; Ma, Lie; Li, Bo; Gao, Changyou
In this study, the highly specific biotin–avidin interaction was used to immobilize DNA complexes to a substrate. An excess of biotin was added to trigger the dissociation of DNA complexes from the substrate to mediate their release and transfection. Biotin-grafted-polyethyleneimine/DNA complexes with N/P ratio of 5 were prepared with diameter of 170.2 nm and ζ-potential of 16.1 mV. The DNA immobilized substrates were fabricated using a biotin–avidin–biotin sandwich model, which were characterized by atom force microscope and fluorescent microscope. Compared to DNA immobilization by physical adsorption, a higher DNA density of 935 ng/cm 2 was observed on biotinylated substrates. Based on the in vitro release profiles, the DNA complexes immobilized on silanized substrate released faster than those on biotinylated substrate. Triggered by the addition of extra biotin, more DNA complexes were released. The transfection efficiencies of the DNA complexes immobilized on different substrates were assayed on HEK-293T cells. The highest transfection efficiency was obtained in the group of biotinylated substrate with the trigger of extra biotin. Thus, the system of demobilized DNA complexes onto a substrate by the biotin–avidin interaction and the dissociation of DNA complexes from a substrate triggered by the extra biotin provides a promising strategy for the realization of the controlled release and enhanced transgene expression of genes.